Evaluation of the cell block technique as an auxiliary method of diagnosing jawbone lesions - Anne Caroline Costa Oenning; Elena Riet Correa Rivero; Maria Cristina Marino Calvo; Maria Inês Meurer; Liliane Janete Grando (Brazilian Oral Research, 2012)
This study investigated the viability of the cell block technique as an auxiliary method of diagnosing jawbone lesions. Thirty-three clinically diagnosed jawbone lesions with a cystic appearance were subjected to aspiration. The aspirated material was processed by the cell block technique, and the lesions were biopsied and treated. Cytological findings (cell block) and histopathology analyses (gold standard) were compared by the chi-square test. There were associations between cysts and cholesterol crystal clefts, between keratocystic odontogenic tumors (KOT) and epithelial cells, and between KOT and parakeratin. The occurrence of cholesterol crystal clefts in cell block slides was correlated with cystic lesions, and the parakeratin presence was a KOT indicator. The cell block technique proved to be fast, easy-to-handle, and low-cost, making it an attractive auxiliary method for the preliminary diagnosis of jawbone lesions.